TINJAUAN YURIDIS TERHADAP TERPIDANA YANG TELAH DIVONIS BERSALAH TANPA AMAR PERINTAH PENAHANAN (Studi Kasus Putusan Nomor 192/Pid.B/2015/PN.Rgt) - Rafika Anggraini; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The decision of Rengat District Court No. 192/Pid.B/2015/PN.Rgt does not fully comply with the pro-visions of the Criminal Event Law (KUHAP) especially Article 197 paragraph (1) letter k, and will certainly cause legal consequences. The purpose of writing this thesis: first, to know the legal certain-ty of convicts who have been convicted without amar restraining orders in Verdict No. 192/Pid.B/2015/PN.Rgt). Second, to find out the legal consequences of a verdict against a convicted felon without amar restraining order in Verdict No. 192/Pid.B/2015/PN.Rgt).The type of research used in this legal research is normative juridical method. Therefore in this research the data analysis used is qualitative analysis. In drawing conclusions the author uses deduc-tive thinking methods that are ways of thinking that draw conclusions from a statement or evidence that is general in nature into a statement of a special nature.From the results of the study, there are two main things that can be concluded. First, the legal certainty of convicts who have been convicted without amar restraining orders in the verdict No. 192/Pid.B/2015/PN.Rgt is actually not met, because the convicted who has in fact been convicted re-mains outside or still in a free state so that there is no guarantee of justice or legal certainty in the verdict. Verdict No. 192/Pid.B/2015/PN.Rgt does not contain Article 197 paragraph (1) letter k of the Criminal Code (KUHAP) does not provide legal certainty, so the purpose of the law itself is not achieved because the true criminal law is legalistic. Second, as a result of the law of the verdict that does not include Article 197 paragraph (1) letter k of the Criminal Event Law (KUHAP) as the verdict of case No. 192/Pid.B/2015/PN.Rgt) among others: By itself the verdict is null and void, any verdict that is null and void is an invalid verdict and was originally considered to have never existed, Such a verdict is not binding so that the verdict is not attached to the executive force (non-executive), if the public prosecutor executes it means that the act is arbitrary and unconstitutional and violates human rights because it is contrary to Article 28D paragraph (1) and Article 28J of the Constitution of the Republic of Indonesia as well as Article 17 and Article 34 of Law No. 39 of 1999 on human rights.Keywords : Restraining Order – Article 197 of the Criminal Code – Legal Certainty